Screening and health promotion for non-communicable diseases, malignancies and associated risk factors in integrated child development services functionaries of Panvel Taluka, Maharashtra - Srivastava, Garima; Wadke, Rishikesh; Wanje, Sudhir; Raut, Sonal; Pisharam, Krishnaja Naduvilpatt; Phadnis, Kranti (International Journal Of Community Medicine And Public Health, 2025)
Background: Anganwadi workers play an important role in providing health care to mother and child. As an appreciation to their contribution, ‘Screening and Health Promotion Project’ was launched. Objectives of this study were to study the prevalence of hypertension and diabetes. To screen for oral cancer, breast malignancies cervical cancer. Associated risk factors with the above NCDs. Health promotion by T.A.L.K method. Methods: It was an observational study with an all-inclusive sample of 315 Anganwadi Sevikas and Madatnis from randomly selected 3 PHCs of Panvel Taluka for one year. Modified community-based assessment checklist form was used for data collection. Descriptive statistics Chi Square and t test were applied using Microsoft Excel and SPSS 27 for statistical analysis. Results: Amongst all the participants raised blood sugar was found in 12.69%, raised blood pressure in 13.96%, and high stress in 49% of participants. The less than 39 years aged participants had 44% of the raised B. S, 42.8% of raised BP, 41% of the higher stress. Consumption of smokeless products was strongly related to High Blood Pressure P 0.019. Two known cases of breast cancer and one case of cervical cancer were found. Pap Smear test detected bacterial vaginosis in 18.36% and inflammation in 42.8% of the participants providing consent. Conclusions: The younger strata of Anganwadi workers presenting noticeable increase in B.S, B.P, obesity and stress highlights the need of early and periodic screening, health promotion and awareness sessions for NCDs and malignancies.